PTH-089 Impact of Seasonal Variation on Course of Inflammatory Bowel Disease and Effect of Date of Births on the Onset of Disease: A Fact or a Myth!. (4th June 2013) - Mahmood, R; Slater, J; Wood, L; Anwar, M; Muhammad, H; Cooper, S; DeSilva, S; Shetty, S; Fisher, N C; Ishaq, S
Abstract : Introduction: Effect of seasonal variation on the natural history of the inflammatory bowel disease (IBD) is now well known. Also births in certain time of the year may have an impact on the onset of inflammatory bowel disease later in life. We reviewed our cohort with inflammatory bowel disease over the last four years to look for any such association. Methods: Data collection was retrospective over the last 4 years using IBD database and medical records. Clinical and demographic details of newly diagnosed patients with IBD were recorded. Aims: Our aim was to identify any evidence of seasonal variability on natural history of IBD and to identify any link between the onset of IBD symptoms and the date of births. Results: We had 279 newly diagnosed cases of inflammatory bowel disease during the last 4 years (2008–2011). There was incremental rise in the incidence of disease during this period and majority of the cases had UC (70% UC, 30% CD). There was no consistent correlation of incidence of IBD in any particular season over the last four years (p value = 0.065). Furthermore, there was no consistency in the data for the birth dates pattern and the onset of disease symptoms in our cohort. Conclusion: In our retrospective cohort study we could not demonstrate seasonal variability or impact of date of birth on disease onset but ongoing prospective data collection over a longer period of time may help explore this association. Disclosure of Interest: None Declared. References: Lewis JD, Aberra FN, Lichtenstein GR, Bilker WB, Brensinger C, Strom BL. Seasonal variation in flares of inflammatory bowel disease.Gastroenterology. 2004 Mar; 126(3):665–73. Haslam N, Mayberry JF, Hawthorne AB, Newcombe RG, Holmes GK, Probert CS. Measles, month of birth, and Crohn's disease. Gut. 2000 Dec; 47(6):801–3.